COX-2, CB2 and P2X7-immunoreactivities are increased in activated microglial cells/macrophages of multiple sclerosis and amyotrophic lateral sclerosis spinal cord. - Yiangou, Y; Facer, P; Durrenberger, P; Chessell, I; Naylor, A; Bountra, C; Banati, R; Anand, P (2006)
BACKGROUND: While multiple sclerosis (MS) and amyotrophic lateral sclerosis (ALS) are primarily inflammatory and degenerative disorders respectively, there is increasing evidence for shared cellular mechanisms that may affect disease progression, particularly glial responses. Cyclooxygenase 2 (COX-2) inhibition prolongs survival and cannabinoids ameliorate progression of clinical disease in animal models of ALS and MS respectively, but the mechanism is uncertain. Therefore, three key molecules known to be expressed in activated microglial cells/macrophages, COX-2, CB2 and P2X7, which plays a role in inflammatory cascades, were studied in MS and ALS post-mortem human spinal cord. METHODS: Frozen human post mortem spinal cord specimens, controls (n = 12), ALS (n = 9) and MS (n = 19), were available for study by immunocytochemistry and Western blotting, using specific antibodies to COX-2, CB2 and P2X7, and markers of microglial cells/macrophages (CD 68, ferritin). In addition, autoradiography for peripheral benzodiazepine binding sites was performed on some spinal cord sections using [3H] (R)-PK11195, a marker of activated microglial cells/macrophages. Results of immunostaining and Western blotting were quantified by computerized image and optical density analysis respectively. RESULTS: In control spinal cord, few small microglial cells/macrophages-like COX-2-immunoreactive cells, mostly bipolar with short processes, were scattered throughout the tissue, whilst MS and ALS specimens had significantly greater density of such cells with longer processes in affected regions, by image analysis. Inflammatory cell marker CD68-immunoreactivity, [3H] (R)-PK11195 autoradiography, and double-staining against ferritin confirmed increased production of COX-2 by activated microglial cells/macrophages. An expected 70-kDa band was seen by Western blotting which was significantly increased in MS spinal cord. There was good correlation between the COX-2 immunostaining and optical density of the COX-2 70-kDa band in the MS group (r = 0.89, P = 0.0011, n = 10). MS and ALS specimens also had significantly greater density of P2X7 and CB2-immunoreactive microglial cells/macrophages in affected regions. CONCLUSION: It is hypothesized that the known increase of lesion-associated extracellular ATP contributes via P2X7 activation to release IL-1 beta which in turn induces COX-2 and downstream pathogenic mediators. Selective CNS-penetrant COX-2 and P2X7 inhibitors and CB2 specific agonists deserve evaluation in the progression of MS and ALS.